Clinincal variants of trancient neurological deficit in patients with the neck osteochondrosis. - I. S. Zozulia; V. G. Nesukai (Medičnì Perspektivi)
With the purpose of studing frequency and variability of clinical symptoms there were observed 130 patients after transient ischemic attack (TIA) in a vertebrobasillar pool  (VBP) on a background of neck osteochondrosis, verified from MRI, CT data or sciagraphies of the neck portion of the spine with functional tests. The analysis did not include patients with the signs of acute or past chronic stroke. After systematization of complaints  and symptoms four clinical syndromes were selected: ophthalmic (OPS), vestibuloatactic (VAS), cochleovestibular (CVS) and  local neurological symptoms (LNS) among which VAS and CVS appeared in 27.9 and 31.2% of young patients, respectively, and in 33.3 and 27.3% of the elderly ones. In patients with OPS, visual impairment was more frequent (in 63.6% of patients) and predominantly in women with a frequency of 62.5%, in patients with VAS - dizziness, which occurred in 74.2% of women and 90.0% of men, with  CVS - noise in the ear (68.4%) without a gender difference, in patients with LNS the frequency of hemiparesis/hemiplegia was 34.5% and prevailed in patients of the older age group (50.0 versus 15.4% in young patients).